Information Quality and Market Efficiency - Ho, Thomas S. Y.; Michaely, Roni (Journal of Financial and Quantitative Analysis, 1988)
The purpose of this paper is to analyze the optimal individual behavior in acquiring information and to determine the amount of information incorporated in a stock at equilibrium, in the presence of a cost schedule in acquiring information. Our paper shows that at equilibrium the cost to acquire information that is not already incorporated in the price depends only on the representative investor's risk preferences. It follows that the marginal information costs are the same across all stocks at equilibrium even though the stock's information costs schedules may differ. This suggests that the prices of small stocks may not incorporate all publicly available information. This paper also provides empirical evidence that newspapers' publication of publicly available information can affect the stock prices.